Illness Perception and Self-Care in Coronary Heart Disease Patients: A Cross-Sectional Study - Mailani, Fitri; Nurikhsani, Nadiya; Muthia, Rahmi (Talenta Publisher, 2023)
Relapse and rehospitalization are common occurrences in patients with coronary heart disease (CHD), and these can be mitigated through effective self-care practices. Positive illness perceptions play a crucial role in promoting good self-care. This study aimed to investigate the connection between illness perception and self-care among patients with coronary heart disease at the Cardiac Polyclinic of RSUP Dr. M. Djamil Padang. Conducted from June to July 2023, this quantitative research utilized a cross-sectional approach and involved 242 patients from the cardiac polyclinic at Dr. M. Djamil Padang, using purposive sampling. The instruments used were the Self-Care Coronary Heart Disease Inventory (SC-CHDI) and the Brief Illness Perception Questionnaire (B-IPQ). The mean values for illness perception and self-care were 52.27 (SD=9.76) and 62.31 (SD=11.35), respectively. Data analysis used the Spearman Rank correlation test, yielding a p-value of 0.014 (r=0.157). The findings revealed a positive correlation, indicating a relationship between illness perception and self-care in patients with coronary heart disease. This implies that a more optimistic perception of the disease is associated with improved self-care among CHD patients. It is advisable for individuals with coronary heart disease to enhance their perception by engaging in informational support activities, thereby fostering optimism, and ultimately improving self-care behavior.